Sistem Pendukung Keputusan Penerima Bantuan Langsung Tunai Menggunakan Metode Promethee - I Nyoman Tri Anindia Putra; Ketut Sepdyana Kartini; I Gede Iwan Sudipa; Fajar Muharam; I Made Muryasa (LPPM STIKOM Tunas Bangsa, 2023)
The economy is an important factor in human life. to meet human needs. The economic problem that is often faced by the Indonesian state is poverty. The problem of poverty is complex, so it is always a priority for the government. So far, the Indonesian government has implemented many programs to reduce child poverty, and one of them is direct cash assistance. Direct Cash Assistance is assistance provided by the government to the poor to ease the burden on society and reduce poverty. In the process of selecting people who receive direct cash assistance, they often use manual methods that result in direct cash assistance because they are not on target. To complete and simplify the process, a decision support system is needed that can make the selection process more accurate and fast. A decision support system is a system that is intended to assist decision makers by utilizing certain data and models to solve various unstructured problems. The purpose of this research is to make a decision support system using the PROMETHEE method, which is expected to help determine the priority of beneficiaries of direct cash assistance. The PROMETHEE method is used because this method is able to make better rankings and calculations based on alternatives, criteria, weight values, multi-criteria, inflow, outflow, and net flow values so as to obtain optimal and satisfying results.